Maternal mortality in Lao Peoples, Democratic Republic. - Estudillo, Jonna P.
Lao People?s Democratic Republic (PDR) has the highest maternity moratality ration (MMR-deaths per 1,000 live births) in Southeast Asia. This MMR remains high because of the high inequality in the uptake of critial maternal health services. The least advantaged women have lagged behind the most advtantaged in terms of ante-natal care and delivery care. The delcine in MMR could be attributed to various government social helath protection programs that eased the financial constraint posed by the high out-of-pocket payments in maternal health care.